Investigation On Optical Fibre Configurations For Process Tomography - Ibrahim, Sallehuddin (Penerbit UTM Press, 2002)
This paper describes an investigation on the optimum optical fibre sensing configurations to be utilised for a tomography process system. The response of the sensors was based on two models:- (1) optical attenuation model due to material with differing optical densities, and (2) optical path length model which is used for opaque solids in air or liquid. The circular flow pipe is mapped onto an eight by eight rectangular array of pixels. An investigation is carried out on four flow models: a single pixel flow, two pixels flow, half flow and full flow models. Various arrangements of the fibre sensors are considered for different projections. The forward problem is solved for all combinations of flow model and sensor arrangement. Linear back projection (LBP) algorithm is used to reconstruct the image. A modified reconstruction algorithm combining LBP and a priori knowledge is outlined. Numerical tests, based on the reconstruction, are used to identify the best system to be implemented in hardware.